Using hydrogen as potential fuel for internal combustion engines: A comprehensive assessment - Long Huynh, Diep Ngoc; Nguyen, Thanh Hai; Nguyen, Duc Chuan; Vo, Anh Vu; Nguyen, Duy Tan; Nguyen, Van Quy; Le, Huu Cuong (International Journal of Renewable Energy Development, 2025)
This comprehensive review explores the feasibility and potential of using hydrogen gas as a fuel for internal combustion engines, a topic of growing importance in the context of global efforts to reduce greenhouse gas emissions and transition towards sustainable energy sources. Hydrogen, known for its high energy content and clean combustion properties, presents a promising alternative to traditional fossil fuels. This paper examines the chemical properties of hydrogen and its benefits over conventional fuels, particularly focusing on the technological advancements and modifications required for compression ignition and spark ignition engines to efficiently utilize hydrogen. The review delves into the necessary engine design modification, fuel injection systems, combustion characteristics, and emission control technologies specific to both compression ignition and spark ignition engines. Furthermore, it addresses the environmental impacts, including reductions in greenhouse gases and other pollutants, and evaluates the economic implications, such as production costs and feasibility compared to other energy solutions. Key challenges associated with the storage, distribution, and safety of hydrogen are discussed, along with potential solutions and innovations currently under investigation. This paper aims to provide a thorough understanding of the current state of hydrogen as a promising fuel for internal combustion engines, guiding future research and development in this vital field.